2011
DOI: 10.1111/j.1365-2702.2011.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in handling elder abuse in community care. An exploratory study among nurses and care coordinators in Norway and Australia

Abstract: Community care agencies in both countries need to be aware of the huge impact of the managers' involvement and the services' responsibility and capacity to support professionals in the handling of elder abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 17 publications
0
18
0
10
Order By: Relevance
“…Perhaps they believed that the context of providing home-based services is 'inherently and unavoidably unpredictable and therefore risky' [13, p. 385]. A further challenge was a lack of support, with practitioners calling for more guidance and support from organisational policies and managers, a view echoed by Sandmoe et al [1] who identify the important role of managers in helping workers cope in situations of ongoing elder abuse. In terms of support, practitioners in this study were also frustrated to find that organisations such as family violence services were largely not interested in providing support to older people, a problem that has been emphasised by other commentators [14].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps they believed that the context of providing home-based services is 'inherently and unavoidably unpredictable and therefore risky' [13, p. 385]. A further challenge was a lack of support, with practitioners calling for more guidance and support from organisational policies and managers, a view echoed by Sandmoe et al [1] who identify the important role of managers in helping workers cope in situations of ongoing elder abuse. In terms of support, practitioners in this study were also frustrated to find that organisations such as family violence services were largely not interested in providing support to older people, a problem that has been emphasised by other commentators [14].…”
Section: Discussionmentioning
confidence: 99%
“…None of the participants in our study expressed a desire to have no further contact with their offspring, and those who had lost contact with part of their family reported emotional distress. Therefore, it is imperative that professionals identify the ties in the abusive relationship at an early stage and what the victim wants to achieve by seeking professional assistance 33,34…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not evident in the study. [42] Schmeidel et al (2012) [43] examined the perspectives of healthcare professionals on detection and reporting of elder abuse. Nurses and physicians were not as knowledgeable of elder abuse matters compared with social workers, and nurses were unsure of their role.…”
Section: Introductionmentioning
confidence: 99%
“…Both Swedish and Japanese nurses despite cultural differences showed a global 'humanness' to the issue of elder abuse. [42] reported that intuition and experience were key factors in identification of suspected elder abuse cases. Clinical assessment was informed by ability of the nurse to observe home situation of client; quality of the information gathered about clients; support of manager and alliances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation